PREVALENCE AND ANTIBIOTIC SUSCEPTIBILITY PATTERN OF GRAM NEGATIVE BACILLI ISOLATED FROM URINARY TRACT INFECTIONS - KHAN , JA; QAMAR , K; GOHAR , F; AHMAD , J; BANO , S; FAROOQ , K (Biological and Clinical Sciences Research Journal, 2024)
The aim of the study was to find out the prevalence and antibiotic susceptibility pattern of Gram negative bacilli isolated from urinary tract infections. This cross-sectional study was conducted at the department of urology Lady reading hospital Peshawar from February 2021 to August 2023. Mid-stream urine samples were collected from individual having the symptoms of urinary tract infection and were processed and identified through various biochemical tests. Following CLSI recommendations, the isolated bacteria were screened for sensitivity to antibiotics. Kirby-Bauer disc diffusion method was used in the current study. Through MS Excel, data were analyzed. The Chi-square test was applied for calculating the p value (significant i.e. <0.05) and antibiotic resistant profiles of GNB isolated from urine samples. A total of 60000 urine samples were collected in which 65% (n=3900) patients were outdoor and 35% (n=2100) were hospitalized patients. Among them 20 % (n=1200) were culture positive. Among which 58% urine samples were from outdoor patients and 42% samples were from hospitalized patients. E.coli, Klebsiella pneumonia, P. aeruginosa and Acinetobacter baumannii were the Gram negative bacilli (GNB) isolated in our study. The most prevalent (72%) GNB was E. coli. Pseudomonas aeruginosa isolated from indoor patients’ urine samples showed high resistance. The antibiotic sensitivity pattern of K. Pneumonia was same as E.coli both in out and indoor patients. The .Acinetobacter baumannii resistance pattern was quite lower observed as 85% in Nitrofurantoin (F), 80% in Ampicillin (AMP) and 11% in Fosfomycin (FOS) respectively in urine samples of indoor as compare to outdoor patient. The most prevalent GNB observed in our study were E. coli, Klebsiella pneumonia, P. aeruginosa and Acinetobacter baumannii involved in UTIS. The choice of antibiotic for its treatment were Fosfomycin, Piperacillintazobactam, Cefoperazone-sulbactam, Amikacin and Nitrofurantoin.